Kata Yen dalam Bahasa Bali: Suatu Tinjauan Sederhana - Teguh, I Wayan (Humanis, 2022)
The word yén (Balinese) has a meaning parallel to the words if and if (Indonesian). One of the characters of the word yén is as a conjunction. In addition, the word yén also has a character like a preposition. The word yén (Balinese) only has a function and meaning in a syntactic structure. The word yén (Balinese) which functions as a conjunction has similarities and differences with the word yén which is characterized as a preposition. In this case both belong to the category of particles. In addition, it also only has a function and meaning in a syntactic structure. The difference is that yén as a subordinate conjunction connects words or phrases that have the potential to become clauses. On the other hand, yén which is characterized as a preposition is followed by a group of words or words that are potential phrases. That is, the conjunction yén is discussed at the sentence level, while yén which is similar to a preposition is discussed at the phrase or word group level.